The role of time in activation of flow units in metallic glasses. (December 2015) - Ge, T.P.; Gao, X.Q.; Huang, B.; Wang, W.H.; Bai, H.Y.
Abstract: Flow units, which accommodate deformations and initiate transformation from glass to supercooled liquid state, have been proved to significantly influence the properties of metallic glasses (MGs). We study the time dependent activation of the flow units in MGs, and find that the size and the fraction of the flow units increase with the applied time, which lead to the time dependences of the mechanical behaviors, flow phenomenon and relaxations of MGs. A diagram for the flow in glass based on the concept of flow unit, activation time, and imposed energy (stress or temperature) is constructed to understand the deformations and flow mechanisms of MGs. Graphical abstract: Highlights: The time dependent activation of the flow units in metallic glasses. The time dependences of the mechanical behaviors, flow phenomenon and relaxations of metallic glasses. A diagram for the flow in metallic glass.